2021
DOI: 10.1093/jjco/hyab185
|View full text |Cite
|
Sign up to set email alerts
|

Marginal resection for patients with atypical lipomatous tumours of the extremities and trunk wall: a systematic review and meta-analysis

Abstract: Background This systematic review assessed and compared the efficacy of marginal resection to wide resection in patients with atypical lipomatous tumours (ALT) by evaluating the local recurrence rates, overall survival and adverse event rates. Methods We evaluated studies published between 1 January 1990 and 31 January 2019. The risks of bias in the selected studies were analyzed using the Cochrane Collaboration Risk of Bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They have suggested that wide resection is necessary to prevent local recurrence, dedifferentiation, and residual tumor. However, a recent systematic review revealed that the local recurrence rate was not significantly higher in the marginal resection group (32). A scheduled R1 marginal resection is easy because the tumor capsule is completely individualized.…”
Section: Managementmentioning
confidence: 98%
“…They have suggested that wide resection is necessary to prevent local recurrence, dedifferentiation, and residual tumor. However, a recent systematic review revealed that the local recurrence rate was not significantly higher in the marginal resection group (32). A scheduled R1 marginal resection is easy because the tumor capsule is completely individualized.…”
Section: Managementmentioning
confidence: 98%